An Analytical Study of English Collocations Usage in the Book of Dialogues of the Buddha by T.W. Rhys Davids Vol 1 - Candima; Kanokkamalade , Veerakarrn; Pintrymool, Narongchai (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2021)
The objectives of this study were (1) to study the English collocations usage of the keywords in Buddhist literature, Dialogues of the Buddha by T.W. Rhys Davids Vol 1, and (2) to analyze the types of combinations pertaining to the English collocations usage of the keywords in selected Buddhist literature Dialogues of the Buddha by T.W. Rhys Davids Vol 1. The results revealed were 1) The keywords knowledge had the most frequent usage of English collocations in Dialogues of the Buddha volume 1 by T.W. Rhys Davids with the frequency of 42 or 7.83 %. Among the frequency of 42 occurrences, the result was as follows: knowledge of with the frequency of 42 or 7.83%. 2) The Noun + Preposition was the most frequent type of combination pertaining to the usage of English collocation of the keyword in Dialogue of the Buddha volume 1 by T.W. Rhys Davids with the frequency of 207 or 38.61%. The Buddhist literature, Dialogues of the Buddha by T.W. Rhys Davids volume 1, exploitation and expectation of the Buddha teaching in Buddhist’s literature, was selected. The data was initially collected and analyzed by application of the software Ant Conc 3.5.8. (Windows) 2019 which was developed by L. Anthony. The study was followed by utilizing Microsoft Excel 2016 data base, Oxford Collocations Dictionary for students of English (2012), and Longman Collocations Dictionary and Thesaurus (2013). The results derived from the current study through a documentary and qualitative method revealed a list of keywords which were most frequently used in Dialogues of the Buddha volume 1 by T.W. Rhys Davids. From the selected top 50 most frequent keywords, the collocations to each keyword were identified. Only the English collocations usage of that met specified criteria were selected and categorized into 17 types of combinations pertaining to the usage of English Collocations. That among the seventeen types of combinations, the Noun + preposition was the most frequent type of combinations relating to the usage of English collocations of the keywords in Dialogues of the Buddha vol 1 by T.W. Rhys Davids, with the frequency 0f 207 occurrences or 38.61 %. However, the verb + phrase was the least frequent types of combinations with the frequency of 3 occurrence or 0.55 %. The Noun + Noun, Quantifier + Noun, Verb + Adjective, Noun + Verb, Verb + Adverb, Adjective + Phrase, and Adverb + Verb of combinations showed no frequency of occurrence at all.